Pelatihan Manajemen Stress untuk Mengurangi Stress Relawan Komunitas Berbagi Cerita Indonesia - Farisandy, Ellyana Dwi; Pontoh, Jennifer Shalom (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Volunteers are prone to experiencing stress due to the enormous workload they face. Stress on volunteers must be appropriately managed so that it does not impact daily life. This research was conducted to see the effectiveness of stress management training in reducing stress in the Berbagi Cerita Indonesia Community. This training uses a one-group pretest-posttest research design. Selection of participants using purposive sampling. There were nine participants involved in this study. Researchers developed a measuring tool to measure knowledge about stress, while the measuring tool for stress was calculated using the DASS (Depression, Anxiety, and Stress Scale). The collected data were analyzed using a paired sample t-test. The results show a significant difference between before and after the training. This explains that stress management training is practical in enhancing knowledge about stress for the Berbagi Cerita Indonesia Community volunteers.